Principal Management in Implementing the Deep Learning Approach to Improve Educational Quality at SMA Negeri 1 Penajam Paser Utara - Dinda Ruszayanthi; Masrur Yahya; Moh Bahzar; Widyatmike Gede Mulawarman; Usfandy Haryaka; Akhmad Akhmad (International Journal of Education, Vocational and Social Science, 2026)
This study examines the principal's management in implementing the deep learning pedagogical approach to improve educational quality at SMA Negeri 1 Penajam Paser Utara. The research was motivated by the need to strengthen 21st-century competencies, character development, and meaningful learning in the context of Indonesia's Merdeka Belajar (Freedom to Learn) curriculum policy. Employing a qualitative case study design, data were collected through in-depth interviews, observation, and documentation analysis involving the school principal, vice principal for curriculum affairs, teachers, the school committee, and students. Data were analyzed using Miles and Huberman's interactive model: data reduction, data display, and conclusion drawing. The findings reveal that the principal's management in implementing deep learning was executed strategically across four management functions: (1) Planning the principal integrated deep learning principles into the School Operational Curriculum (KOS), lesson plans, and teacher professional development programs, with sensitivity to student diversity including student athletes; (2) Organizing collaboration was strengthened through internal subject teacher forums (MGMP), academic supervision, and a school quality assurance team, reflecting principles of distributed leadership; (3) Implementing learning shifted toward student-centered activities including project-based learning, contextual discussion, formative assessment, and reflective practice, enhancing student engagement and critical thinking; (4) Evaluating comprehensive and participatory evaluation involving teachers, students, and the school committee served as the basis for continuous improvement and evidence-based decision making. The study concludes that visionary, collaborative, and instructionally-focused principal leadership is the key determinant in successful deep learning implementation and educational quality improvement.